Sensors and computational fluid dynamics (CFD) data fusion for air flow and temperature estimation - Yee, Daniel En Hao (2018)
This final year report presents the results on the behavior of air flow and temperature in an enclosed environment. The aim of the project is to obtain a method to integrate the analysis results of air flow and temperature in a simulated environment, into a real enclosed environment setting. This will greatly reduce the time needed when research areas or studies involving air flow and temperature is required, as the user does not need to carry out actual experiments to acquire these results. With the aid of ANSYS Fluent, a program that is suitable in Computational Fluid Dynamics (CFD) analysis, simulations can be configured, with suitable boundaries conditions to achieve the appropriate results on the behavior of air flow and temperature. These results will be interpolated to fit the actual environment with minimal errors. In this report, the reader will be able to understand how the simulations are being designed and carried out, as well as how the interpolation results are obtained.